21.1k views
1 vote
The substitution method: Solve for x in the second equation and substitute it into the first equation. The result is .

2 Answers

2 votes

Answer: solve for c in a second equation and substitute: correct is 2(-3+2y) +5y= -6. 100% correct.

Explanation:

User Bubble Hacker
by
5.2k points
4 votes

Suppose you have the following system of linear equation:



\left \{ {{(1) \ ax+by=c} \atop {(2) \ dx+ey=f}} \right.


According to the statement above, first we need to solve for x in the second equation:



dx+ey=f \\ \\ \therefore x=(f-ey)/(d)


Next we need to substitute x into the first equation, so:



a\left((f-ey)/(d)\right)+by=c


So, the conclusion is that from this last equation the result we can get is y. Then, by substituting the value of y in the first or second equation we can get x.

User Sloan Thrasher
by
5.5k points